TCU Based Fast Testing Platform for Automated Manual Transmission - Ranjan Mahapatra, Tapas; Ranjan Swain, Biswa (International Journal of Psychosocial Rehabilitation, 2025)
To lower the time of development cycle and transmission controlling unit (TCU) cost for automatic manual transmission (AMT), a “rapid testing platform (RTP)” in light of the idea of hardware loop simulation is presented and executed in this paper. The proposed RTP highlights that the vehicle parts in reproduction are on the whole model-based. Torque characteristics for the engine, the mechanical quality of the DC engine, and the torque moving trait of grip are talked about. By numerical demonstrating, simulators of vehicle movement, clutch, actuators, engine and gearbox that form the RTP for TCU are created. Through the technique of signal processing, those simulators have been embodied in an embedded system with functioning networks. Experiments with an outcome of TCU are conceded and simulating outcomes shows that RTP is capable of simulating the vehicle conditioning and behaviour approx. well.